A Review on Outcomes of Distal Radius Fracture Treated With Different Modes of Treatment and Rehabilitation - Asad Aziz; Aqeel Ahmed Memon; Idress Shah; Imtiaz Hashmi; Sohial Rafi (ziauddin University, 2020)
Fractures around wrist joint are common complication happening after fall on an outstretched hand. It is more common in female, and mostly in age above 55 years. Different methods of treatment has been established such as surgical and conservative management, each mode of treatment has its own complication such as, pain, stiffness, swelling, deformity, infection. Non operative treatment include splinting or casting with or without reduction, operative treatment includes percutaneous k-wiring, external fixator for complex fracture or fracture with open wound, open fixation with volar or dorsal plate. Still there is controversy that what method is better in getting the good functional outcome, minimizing the duration of cast immobilization, early fixation, and early start of rehabilitation. All of them play part in better functional outcome. In the past manipulation and fixation without opening the fracture site has been the choice of treatment, comparatively in recent advances fixation with plate through anterior approach is a preferred option because it has less complication rate, plays better role in early range of movement. The information was retrieved from reliable search engines e.g. PubMed, Medline, Google scholar and others, through original research papers and reviews from2003 to 2019. Purpose of this study is to know which method of management has better outcome and its role in early rehabilitation.